2022
DOI: 10.3390/jcm11051461
|View full text |Cite
|
Sign up to set email alerts
|

Large Cell Neuroendocrine Carcinoma of the Lung: Current Understanding and Challenges

Abstract: Large cell neuroendocrine carcinoma of the lung (LCNEC) is a rare and highly aggressive type of lung cancer, with a complex biology that shares similarities with both small-cell lung cancer (SCLC) and non-small-cell lung cancer (NSCLC). The prognosis of LCNEC is poor, with a median overall survival of 8–12 months. The diagnosis of LCNEC requires the identification of neuroendocrine morphology and the expression of at least one of the neuroendocrine markers (chromogranin A, synaptophysin or CD56). In the last f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 108 publications
1
47
0
Order By: Relevance
“…Recent studies on the basal cell origin of pulmonary tuft cells might explain this finding, which supposed that the genomic profiles of SCLC, LCNEC, and SCC overlap slightly. 15,32,33 This finding suggested that the biological relationship between SCLC/LCNEC and basaloid SCC was much closer than what we realized currently. Thus, the addition of p40/p63 to exclude the possibility of basaloid SCC is an important decision in NE-negative carcinomas where the diagnosis of SCLC is being considered.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recent studies on the basal cell origin of pulmonary tuft cells might explain this finding, which supposed that the genomic profiles of SCLC, LCNEC, and SCC overlap slightly. 15,32,33 This finding suggested that the biological relationship between SCLC/LCNEC and basaloid SCC was much closer than what we realized currently. Thus, the addition of p40/p63 to exclude the possibility of basaloid SCC is an important decision in NE-negative carcinomas where the diagnosis of SCLC is being considered.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, we found that POU2F3 was positive in SCC and LCNEC, while POU2F3 expression was consistently negative in all tested lung adenocarcinomas, NSCLC-NOSs, NUT carcinomas, SMARCA4-UT and atypical carcinoids. Recent studies on the basal cell origin of pulmonary tuft cells might explain this finding, which supposed that the genomic profiles of SCLC, LCNEC, and SCC overlap slightly 15,32,33 . This finding suggested that the biological relationship between SCLC/LCNEC and basaloid SCC was much closer than what we realized currently.…”
Section: Discussionmentioning
confidence: 46%
“…1 B,E), which confer additional survival benefit, as documented for both ALK+ and wild-type NSCLC ( Weickhardt et al 2012 ; Rheinheimer et al 2020 ). Emerging strategies to further improve outcome of ALK+ LCNEC could be the upfront use of more potent, next-generation ALK inhibitors instead of crizotinib ( Mok et al 2020 ; Camidge et al 2021 ; Solomon et al 2022 ); closer patient surveillance using serial liquid biopsies to detect disease progression earlier ( Angeles et al 2021 ), monitor acquired resistance ( McCoach et al 2018 ; Dietz et al 2020 ), and inform the choice between local ablation versus systemic therapy switch in case of oligoprogression ( Christopoulos et al 2021 ); use of PD-(L)1 inhibitors, which are associated with longer OS compared to chemotherapy in several retrospective analyses of LCNEC ( Dudnik et al 2021 ; Fisch et al 2021 ); and implementation of novel, experimental compounds, such as the upcoming fourth-generation ALK TKI and drugs directed against other signaling pathways ( Christopoulos et al 2017 ; Ou et al 2021 ; Andrini et al 2022 ). At the same time, it should be noted that many of these approaches remain experimental without proven survival benefit and warrant systematic examination in prospective studies before wide adoption, as, for example, recently outlined by the U.S. Food and Drug Administration (FDA) in the guidance document on the integration of circulation tumor DNA (ctDNA) assays in clinical research ( FDA 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of SCLC, the annual incidence of other lung NENs has been steadily increasing, probably attributable to the progressive ageing of the population, to the improvements of diagnostic techniques 4 and the greater awareness of these entities in the broader medical community 7,8 …”
Section: Introduction To Lung Neuroendocrine Neoplasms: Terminology A...mentioning
confidence: 99%